การพัฒนาความสุขครัวเรือนด้วยอัตลักษณ์วิถีพอเพียงของกลุ่มชาติพันธุ์ไทย-ลาว ในราชอาณาจักรไทยและสาธารณรัฐประชาธิปไตยประชาชนลาว - ภูวันทมาตย์ , สนองวิชญ์ (Journal of Human and Society, Sisaket Rajabhat University, 2022)
การศึกษาวิจัย เรื่อง การพัฒนาความสุขครัวเรือนด้วยอัตลักษณ์วิถีพอเพียงกลุ่มชาติพันธุ์ไทลาวในราชอาณาจักรไทยและสาธารณรัฐประชาธิปไตยประชาชนลาวมีวัตถุประสงค์เพื่อ 1) ศึกษาบริบทอัตลักษณ์ความสุขครัวเรือนวิถีพอเพียงของกลุ่มชาติพันธุ์ไทลาว ในราชอาณาจักรไทย และในสาธารณรัฐประชาธิปไตยประชาชนลาว 2) เพื่อศึกษากระบวนการพัฒนาความสุขครัวเรือนด้วยอัตลักษณ์ความสุขครัวเรือนด้วยวิถีพอเพียงของชุมชน กรณีศึกษา 2 แห่ง คือ โครงการเกษตรทฤษฎีใหม่ในราชอาณาจักรไทยและในสาธารณรัฐประชาธิปไตยประชาชนลาว 3) เพื่อวิเคราะห์องค์ประกอบของอัตลักษณ์ความสุขครัวเรือนที่สัมพันธ์กับวิถีพอเพียงของกลุ่มชาติพันธุ์ไทลาวในราชอาณาจักรไทย และจัดทำข้อเสนอเชิงนโยบายพัฒนาความสุขของครัวเรือนที่ยังยืนของครัวเรือนในภาคตะวันออกเฉียงเหนือ ราชอาณาจักรไทย การวิจัยครั้งนี้ใช้ระเบียบวิธีวิจัยเชิงคุณภาพร่วมกับเชิงปริมาณ งานวิจัยเชิงคุณภาพเป็นการศึกษาโดยการสัมภาษณ์เชิงลึก กลุ่มผู้ใหข้อมูลหลัก ประกอบด้ว กลุ่มผู้นำชุมชน ผู้นำศาสนา ผู้แทนครัวเรือน รวมทั้งสิ้น 32 คน ส่วนการวิจัยเชิงปริมาณ ใช้การสำรวจจากแบบสอบถาม จำนวน 500 ชุด ผลการวิจัยพบว่า 1.บริบทของอัตลักษณ์ความสุขครัวเรือนวิถีพอเพียงของกลุ่มชาติพันธุ์ไทลาว ประกอบด้วยบริบทอัตลักษณ์ 7 ด้าน ประกอบด้วย 1) การเรียนรู้และปรับตัวของครัวเรือน 2) การประยุกต์สิ่งที่มีในธรรมชาติเป็นมูลค่าเพิ่ม3)พิธีกรรมและความเชื่อ4) การใช้ภูมิปัญญาที่สืบทอดจากบรรพบุรุษ 5) การพึ่งพาธรรมชาติ 6) การดำเนินชีวิตตามหลักศาสนาและประเพณีอันดีงาม และ 7) การมีส่วนร่วมของชุมชน กระบวนการพัฒนาครัวเรือนให้เกิดความสุขด้วยวิถีพอเพียงของกลุ่มชาติพันธุ์ไทลาวในพื้นที่โครงการเกษตรทฤษฎีใหม่ เป็นกระบวนการส่งเสริมการเรียนรู้ของครัวเรือนด้วยปรัชญาเศรษฐกิจพอเพียง สู่การปฏิบัติเพื่อสร้างความสุข ดังนี้ 1) สร้างการรับรู้และเข้าใจในหลักการของปรัชญาเศรษฐกิจพอเพียง 2) การประยุกต์ใช้เศรษฐกิจพอเพียงในระดับครัวเรือน เพื่อสร้างรายได้ ลดรายจ่าย บนวิถีเกษตรที่เรียบง่าย และ 3) การบูรณาการปรัชญาเศรษฐกิจพอเพียง ร่วมกับทุนทางสังคม ทุนทางธรรมชาติ ทุนทางวัฒนธรรม และฮีต 12 คอง 14 สู่การแก้ไขปัญหา และพัฒนาครัวเรือนให้เป็นสุข 3.องค์ประกอบของอัตลักษณ์ความสุขครัวเรือนที่สัมพันธ์กับวิถีพอเพียงของกลุ่มชาติพันธุ์ไทลาว ในราชอาณาจักรไทย และสาธารณรัฐประชาธิปไตยประชาชนลาว 4 องค์ประกอบ ได้แก่ 1) อัตลักษณ์ “งานครัว” มีนัยสำคัญตั้งแต่ วัด บ้านและโรงเรียน ต้องปลูกฝังสมาชิกให้เห็นความสำคัญของ “งานครัว” 2) อัตลักษณ์การเชื่อมความสัมพันธ์ บ้าน-วัด- โรงเรียนหรือส่วนราชการ โดยเริ่มต้นที่ “ฮีตคอง” ที่สัมพันธ์กับบุญประเพณี 12 เดือน 3) อัตลักษณ์การอยู่ร่วมกัน ต้องสัมพันธ์พึ่งกันและกันคำว่า “สบายดี” และ 4) อัตลักษณ์ 5 พุทธวิธี คือ สวดมนต์ น้ำมนต์ ยาธรรมชาติ (สมุนไพร) ฟังธรรม ตั้งสัจจะต่อเทพเพื่อรักษาตัว อันเกิดจากการบูชา 2 อย่างร่วมกันคือ พุทธศาสนา และ ฮีต คอง ส่งผลให้ครัวเรือนเกิดความสุข กระทั้งฝ่ายปกครองไม่ต้องใช้กฎหมายมาบังคับ แต่สังคมจะเป็นสุขร่วมกันเองด้วยบรรยากาศประนีประนอมและเคารพกัน นำมากำหนดเป็นข้อเสนอแนะเชิงนโยบาย 4 ข้อ ได้แก่ 1) ส่งเสริมให้ครัวเรือนในภาคตะวันออกเฉียงเหนือฟื้นฟู อัตลักษณ์ความสุขของครัวเรือนในชุมชนด้วยฮีต 12 คอง 14 2) ส่งเสริมความสัมพันธ์ของสมาชิกในชุมชนผ่านกระบวนการ บ้าน-วัด-โรงเรียน บนพื้นฐานของฮีตคองผ่านบุญประเพณี 12 เดือน 3) ส่งเสริมบทบาทพ่อแม่ในครัวเรือนปลูกฝังจิตสำนึกให้แก่เด็กและเยาวชนให้รู้จักและเคารพกติกาสังคมตามครรลองฮีตคอง และพุทธศาสนา ผ่านข้อปฏิบัติของฮีตคอง และพิธีกรรมทางศาสนา และ 4) ส่งเสริมให้ครัวเรือนทำทานสร้างคุณค่าทดแทนแรงงาน ปฏิบัติตามฮีตคอง ข้อขะลำ และแนวปฏิบัติ 5 พุทธวิธีที่เรียบง่ายและพอเพียง The objectives of this study on Household happiness identities with the sufficiency of ethnics groups in the kingdom of Thailand and Lao People's Democratic Republic. The objectives of this study were to, 1) to study the context of Household happiness identities by sufficiency of Tai-Lao ethnics groups in the Kingdom of Thailand and Lao People's Democratic Republic, 2) to study the process of the development of a family unit be happy with Sufficiency in 2 case studies: the new theory agriculture projects in the kingdom of Thailand and Lao Lao People's Democratic Republic. 3 ) To analyze the component of household happiness identities that related to sufficiency of Tai – Lao ethnic group in the kingdom of Thailand and Lao People's Democratic Republic. And to provide an proposal policy to develop a household happiness in the northeastern region in Thailand. The research uses a mixed method with a quantitative and aqualitative methodology. Using the in-depth interviews were developed as research tools for qualitative methodology. The key informants were composed of 36 informants. With the 500 questionnaires were applied in quantitative methodology. The research results were. The context of household happiness identities by of Tai-Lao ethnic group in the Kingdom of Thailand and Lao PDR, Consist of 7 identities 1) Leaning and adaptation of the household. 2) The applied of natural resources with addition values. 3) Rituals and beliefs. 4) The usage of the inherited wisdom. 5) Natural dependency. 6) Living with religious beliefs and traditional ways and 7) The community participation. The process of development on household to be happiness with of Tai Lao ethnic group in the area of a new theory agriculture project was. The process to promote a family learning with economy sufficiency that led to happiness, 1) Build a perception and the understanding of economical sufficieny philosophy. 2) Apply a sufficiency economical in the family level to earn the revenue, reduce the expense on the simple way. And 3) To approach to sufficient economy philosophy with social capital, natural capital, cultural capital and 12 Heet 14 Kong that led to problem solving and developing a household to be happiness. The components of household happiness identities that related to sufficient way of Tai – Lao ethnic group in the Kingdom of Thailand and Lao PDR. Were on 4 components 1) “Cooking” identity which house, temple, and school were taking important roles. 2) relation identities which house, temple, and school or government were taking important roles by implementing “Heetkong”. 3) the identity of living in harmony had to be related and to using the word “sabaidee” and 4) 5 buddhism method identities were praying, holy water, natural herb, listening to Buddhist ‘s teaching, respect to Buddhism Religion and Heetkong that effected to household happiness. Which make the authorities didn’t have to use Law to control the societies, but the societies would be happy under the compromised and respectful that led to 4 suggestion on policies 1) To promote the North-eastern households to implement happiness identity in communities with 12 Heet 14 kong . 2) To promote a relarion of members in the communities by using process of house-temple-school based on Heetkong with 12 months tradition. 3) To promote the parents roles in household to create consciousness for their children to respect social rules and Buddhism ways and Buddhist rituals and 4) To promote a household to make merit that compensate labor value.